Evaluasi Gangguan Jaringan Telepon dengan Kombinasi Metode Fault Tree Analysis dan Failure Mode And Effect Analysis - Nugroho, Andung Jati (Jurnal Ilmiah Teknik Industri, 2017)
Evaluation the disruptions of telephone network uses a method fault tree analysis (FTA) and failure mode and effect analysis (FMEA). By using FTA, the fault events are identified, which contribute causing top level event of jarlokat isolation, jarlokaf isolation, and devices canât function jarlokar. The results of FTA; 8 basic events for jarlokat isolation, 7 basic events for jarlokaf isolation, and 6 basic events for jarlokar devices canât function, that is smallest events. These basic events are analyzed by FMEA it based on value of the risk priority number by knowing severity from failure effect scale, occurrence from causes scale, and detection from control scale. The result FMEA is priorities problem solving in the following order: the drop wire 1x2 broken, the short circuit of housing wire, the short circuit of distribution point, the trans radio broken, the telephone instrument damaged, the primary wire broken, and the secondary wire broken.